Urban Governance im Stadtumbau ostdeutscher Mittelstädte. Governance-Muster im Stadtumbau am Beispiel der IBA-Städte. Bernburg und Weissenfels. - Heinrich, Anna Juliane (Routledge, 2013)
Ziel des Beitrags ist die Untersuchung des Stadtumbaus zweier ostdeutscher Mittelstädte Bernburg und Weissenfels - anhand des analytischen Konzepts "Urban Governance". Dabei werden im Schwerpunkt die Stadtumbauaktivitäten im Rahmen der Internationalen Bauausstellung Stadtumbau Sachsen-Anhalt 2010 betrachtet. Anhand der Analyse des jeweiligen lokalen Stadtumbauprozesses, des institutionellen Einflusses der Bauausstellung, der beteiligten Akteure sowie ihrer Interaktionen wird die Frage beantwortet, welche Governance-Muster sich abzeichneten.

The focal point of this paper is changes of specific patterns of governance in urban renewal processes in mid-sized cities in East Germany. The starting point of the investigation includes assumptions and first findings that indicate that urban shrinkage necessarily leads to a change and diversification of patterns of governance. Using case studies as a base, this paper examines urban governance in the German cities of Bernburg and Weißenfels. Both cities are affected by shrinkage and both participated in the 2010 International Building Exhibition: Urban Redevelopment Saxony-Anhalt, which was aimed at finding qualifications for urban redevelopment processes. In order to analyze governance within the processes of urban renewal for both case studies, schemes of governance analysis were created to examine the planning processes, institutional influences, stakeholders, and their interactions. The paper concludes that, due t o specific framework conditions of urban shrinkage on one hand, and institutional influences on the other, patterns of governance do indeed change over the course of urban redevelopment processes. In both cities, the predominating sovereign approach to urban development was supplemented with cooperative activities. In Bernburg, an extensive cooperation among three stakeholders of the public sector was realized. Changes in Weißenfels included the implementation of enhanced participation for private stakeholders.
Urban governance in urban redevelopment processes in mid-sized East German cities: Patterns of governance in urban redevelopment processes using the IBA cities of Bernburg and Weißenfels as case studies.
Keywords: Stadtplanung; Stadterneuerung; Mittelstadt; Schrumpfung; Institution; Verwaltung; Verwaltungshandeln; Leitbild; Bauausstellung; Planungsprozess; Entscheidungsprozess; Fallstudie; Urban Governance; Stadtumbau; Akteur